Noise-Induced Hearing Loss and Associated Factors Among Vector Control Workers in a Malaysian State. (November 2014) - Masilamani, Retneswari; Rasib, Abdul; Darus, Azlan; Ting, Anselm Su
This study aims to determine the prevalence and associated factors of noise-induced hearing loss (NIHL) among vector control workers in the state of Negeri Sembilan, Malaysia. This was an analytical cross-sectional study conducted on 181 vector control workers who were working in district health offices in a state in Malaysia. Data were collected using a self-administered questionnaire and audiometry. Prevalence of NIHL was 26% among this group of workers. NIHL was significantly associated with the age-group of 40 years and older, length of service of 10 or more years, current occupational noise exposure, listening to loud music, history of firearms use, and history of mumps/measles infection. Following logistic regression, age of more than 40 years and noise exposure in current occupation were associated with NIHL with an odds ratio of 3.45 (95% confidence interval = 1.68-7.07) and 6.87 (95% confidence interval = 1.54-30.69), respectively, among this group of vector control workers.